Examining the psychometric properties of a refined perceived stress scale during the COVID-19 pandemic. Issue 2 (3rd April 2021) - Eubank, Jacob M.; Burt, Kate G.; Orazem, John
Abstract: The Perceived Stress Scale (PSS) measures general life stress and the Impact of Events Scale (IES) measures retrospective stress from a specific event; both have been validated across various audiences and settings. However, neither measure stress during an evolving public health crisis. The aim was to refine the PSS to measure stress during an event (e.g. COVID-19 pandemic) and examine its psychometric properties within a 4-year Hispanic-Serving Institution in the Bronx, NY. Three items from the IES were added to and one PSS item was removed from the PSS-10, creating a new PSS-12. Cronbach's α for the scale was 0.902 for faculty and 0.903 for students, indicating high internal consistency. Factor analyses also supported calculation of two subtotals similarly across groups. The PSS-12 is a valid instrument to measure perceived stress during a public health crisis, particularly among populations that already experience community health disparities.